Kesan perbezaan kepekatan lilin rumpai laut dan tempoh penyimpanan terhadap kualiti lepas tuai cili benggala ( Capsicum Annuum L.) - Ng, Swee Yin (2014)
An experiment was conducted at the Faculty of Sustainable Agriculture Laboratory, University Malaysia Sabah, Sandakan Campus, to investigate the effects of seaweed waxing on the quality of bell pepper, Capsicum annuum L.. The objective of the study was to determine the effects of seaweed waxing and the day of storage on the quality postharvest bell pepper. Seaweed waxing concentration used were 0%, 2%, 3% and 6%, whl7e the storage day were expanding to 12 days. Two-way ANOVA was used to analyse the measured parameters to compare the effects on different concentration of waxing and storage duration. The total of sample are 48 bell peppers. The quantitative and qualitative were taken in 12 days storage are, weight loss, moisture content, firmness, total soluble solid content and ascorbic acid There are 12 bell peppers for every treatments and are measure every three days. This result show the Significant in weight loss, moisture content and firmness (P<0.05). The day of storage are effect the moisture content and firmness. The concentration on 2% show the best result from the 0%, 3% and 6% of concentration. However this method still not sure for the others result of postharvest quality such as ripening rate. Further study must be carried out to the suitable of concentration, to extend the shelf life in room temperature especially and at the same time will maintain the others postharvest quality.vi